Pengaruh Kompos Tandan Kosong Kelapa Sawit dan Larutan Mikroorganisme Lokal Eceng Gondok terhadap Pertumbuhan Tanaman Kedelai(Glycine max L. Merill)pada Tanah Pasca Tambang - aulya Rochimah; Ansyahari Ansyahari; roro kesumaningwati (Mulawarman University, 2019)
The research was conducted to determine: 1) some chemical properties of oil palm empty fruit bunches (EFB) compost withbio-activator of water hyacinth local microorganism solution; 2) the best dose of local microorganism solution and compost of empty fruit bunches on the growth of soybean.The research was conducted from April until November 2016 in the Laboratory of Soil,Faculty of Agriculture,Mulawarman University,Samarinda.The experiment wasarranged in Completely Randomized Design (CRD) with five treatments and fivetime replications. The treatment was dose of compost,consisted of: 0 (control);200;400;600;and 800 g per polybag. Data were analyzed by analysis of variance (Anova) with F-test and if there was significantly different among treatments, continued withleast significant difference (LSD) test of 5%. Results of the chemical properties analysis of oil palm empty fruit bunchescompost with 300 mL local microorganism solution L-1as follows: pH 9.10; Organic-C 35.32%; total-N 1.34%; C/N ratio 26.36%; P2O5 0.08%; and K2O 1.88%.The dose of 800 g compost per polybag is the best dose of compost to the plant height at 14, 21, 28, 35, and 42 days after planting respectively 14.00; 18.32; 21.52; 24.54; and 27.36 cm, number of pods 8.80,and dry seed weight of soybean 1.99 g.